2021
DOI: 10.1128/mbio.01062-21
|View full text |Cite|
|
Sign up to set email alerts
|

More Is Not Always Better—the Double-Headed Role of Fibronectin in Staphylococcus aureus Host Cell Invasion

Abstract: Traditionally, Staphylococcus aureus has been considered an extracellular pathogen. However, among other factors, the frequent failure of antimicrobial therapy and the ability of the pathogen to cause recurrent disease have established the concept of eukaryotic invasion of the pathogen, thereby evading the host’s immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 58 publications
(65 reference statements)
2
20
0
Order By: Relevance
“…This bridge facilitates the recognition between pathogen and host cell, leading to subsequent cell integration [ 162 , 163 , 164 , 165 ]. Although the osteoblasts evidenced high expression of α5β1-integrin and fibronectin, and the bacteria disclosed a high affinity to adhere to osteoblasts, Niemann et al demonstrated, through internalization tests and immunofluorescence microscopy, that S. aureus was less swallowed in osteoblasts compared to epithelial cells [ 166 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…This bridge facilitates the recognition between pathogen and host cell, leading to subsequent cell integration [ 162 , 163 , 164 , 165 ]. Although the osteoblasts evidenced high expression of α5β1-integrin and fibronectin, and the bacteria disclosed a high affinity to adhere to osteoblasts, Niemann et al demonstrated, through internalization tests and immunofluorescence microscopy, that S. aureus was less swallowed in osteoblasts compared to epithelial cells [ 166 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The investigators reported a significant increase in osteoblast uptake of S. aureus , resulting in inhibition of fibril formation, brief reduction in RNA-mediated fibronectin expression, and disruption of the fibronectin–fibril network. From the work of Nieman et al it emerges that the fibronectin–fibril network appears to strongly reduce the absorption of S. aureus in a given host cell, indicating that the supramolecular structure of the fibronectin can direct the different ability of particular host cells to internalize the pathogen [ 166 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…No differences were evident between osteoblasts and osteocytes directly after host cell invasion. A possible mechanism for S. aureus invasion into osteoblasts and osteocytes might be the recognition of α5β1 integrins on host cells through fibronectin binding proteins (FnBPA and FnBPB;Niemann et al, 2021). However, further experiments should be performed to investigate this pathway in the present model.…”
Section: Discussionmentioning
confidence: 98%
“…Between these, evidence proved that IsdB-expressing bacteria bound to both soluble and immobilized vWF. [167] More recently Alfeo et al discovered that the iron-regulated surface determinant B (IsdB) protein, besides being involved in iron transport and vitronectin binding, interacts with von Willebrand Factor (vWF). [168] The researchers found that the bond established between IsdB and the recombinant vWF was stopped by heparin and was reduced due to high ionic strength.…”
Section: Immuno Response and Vaccinementioning
confidence: 99%